ВОЛНЫ ИЛИ ВИХРИ? - Белоненко Т.В.; Захарчук Е.А.; Фукс В.Р. (My University, 1999)
The paper discusses an issue of difference between relative energy inputs from vortexes and low-frequency waves in the sea. Two phenomenological models are considered: a synoptical vortex and a low-frequency wave, where the level rise is analytically prescribed and the flow speed is calculated by hydro-dynamical equation taken in the linear quasi-geostrophical approximation. It is shown that under the pattern of spatial/temporal variation of the observed currents.